Intelligent Accident Detection and Vehicle Security for Two Wheelers - H, David Sherry; D, Manoj Kumar; R, Ritchie Saul Daniel; P, Subramani; D, Prema; Y, Hamsavarthini (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Quick medical assistance in case of accidents aid in saving the lives. The main aim of this developed system is to alert the nearby hospital about the accident and to provide immediate medical aid. The system has various sensors such as accelerometer, vibration and tilt, to identify the variations in the vehicle. The system makes decision based on the value of the sensors and sends the information through smartphones connected to the Raspberry pi module. The vehicle security system uses a fingerprint recognition for ignition of vehicle engine to ensure the protection of the vehicle from unauthorized access.